2021
DOI: 10.1016/j.meegid.2021.104801
|View full text |Cite
|
Sign up to set email alerts
|

Impact of I/D polymorphism of angiotensin-converting enzyme 1 (ACE1) gene on the severity of COVID-19 patients

Abstract: Severe acute respiratory syndrome corona virus-2 (SARS-CoV-2) has first emerged from China in December 2019 and causes coronavirus induced disease 19 (COVID19). Since then researchers worldwide have been struggling to detect the possible pathogenesis of this disease. COVID19 showed a wide range of clinical behavior from asymptomatic to severe acute respiratory disease syndrome. However, the etiology of susceptibility to severe lung injury is not yet fully understood. Angiotensin-converting enzyme1 (ACE1) conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 33 publications
7
69
2
1
Order By: Relevance
“…In India, Verma et al genotyped ACE1 I/D polymorphisms using RT-PCR with a sample of 269 COVID-19 patients and then performed a statistical analysis of the association between COVID-19 symptoms and ACE1 I / D polymorphism [50]. They found that the frequency of the ACE1 DD genotype and D allele was significantly higher in patients with severe COVID-19.…”
Section: Studies With Patient Samples (Clinical Studies)mentioning
confidence: 99%
“…In India, Verma et al genotyped ACE1 I/D polymorphisms using RT-PCR with a sample of 269 COVID-19 patients and then performed a statistical analysis of the association between COVID-19 symptoms and ACE1 I / D polymorphism [50]. They found that the frequency of the ACE1 DD genotype and D allele was significantly higher in patients with severe COVID-19.…”
Section: Studies With Patient Samples (Clinical Studies)mentioning
confidence: 99%
“…Age and sex, indeed, represent non-genetic factors that primarily influence disease severity [69], but not exclusively. Verma et al [70] reported a correlation between ACE I/D (OR = 2.5. Table 1) polymorphism and a cluster of patients affected by diabetes mellitus and high blood pressure.…”
Section: Discussionmentioning
confidence: 97%
“…Viral infection may lead to further suppression of ACE2 function and cause ACE1/ACE2 imbalance responsible for RAAS over-activation and pulmonary shutdown [54] . The ACE1/ACE2 imbalance predicts that COVID-19 patients with the D allele of ACE1, especially the DD genotype, will have a more severe course of the disease, as seen in SARS patients with an ACE1 DD genotype [58] , [59] . An Italian study showed an inverse correlation between the I/I polymorphism and COVID-19-related deaths [60] , whereas others investigated the link between ACE I/D polymorphism and acute pulmonary embolism in COVID-19 pneumonia.…”
Section: Genetic Polymorphisms Affecting the Angiotensin-converting Enzyme 2 Expression ( Table 1 )mentioning
confidence: 99%